Immunogenicity of dimorphic and C-terminal fragments of Plasmodium falciparum MSP2 formulated with different adjuvants in mice. Issue 13 (18th March 2016) - Balam, Saidou; Jafarshad, Ali; Servis, Catherine; Frank, Geraldine; Reed, Steve; Pink, Richard; Druilhe, Pierre; Spertini, François; Corradin, Giampietro
Highlights: Both dimorphic (D) and C region fragments of the two allelic families of MSP2 are immunogenic. The fine specificity and intensity of the antibodies responses are dependent on mouse strains and adjuvants. The major epitopes are restricted to the sequences comprising the last 8 aa of D and first 12 aa of C of the two allelic families and the first 20 aa of the C region. Strong immune responses were associated with GLA-SE adjuvant and its combination with other TLR agonists. And elicited antibodies are active in ADCI for Plasmodium falciparum growth inhibition. Abstract: Background: Plasmodium falciparum MSP2 is a blood stage protein that is associated with protection against malaria. It was shown that the MSP2 dimorphic (D) and constant (C) regions were well recognized by immune human antibodies, and were characterized by major conserved epitopes in different endemic areas and age groups. These Abs recognized merozoite-derived proteins in WB and IFA. Here, the goal was to determine in mice the immunogenicity of the two allelic MSP2 D and C domains formulated with different adjuvants, for their possible use in future clinical studies. Method: Female A/J, C3H, and ICR mice were immunized subcutaneously 3 times at 3-week interval with a mixture of allelic and conserved MSP2 long synthetic peptides formulated with different adjuvants. One week after the third injection, sera from each group were obtained and stored at −20 °C for subsequent testing. Results: Both domains of the two MSP2 families are immunogenic and the fine specificity and intensity of the Ab responses are dependent on mouse strains and adjuvants. The major epitopes were restricted to the 20-mer peptide sequences comprising the last 8 aa of D and first 12 aa of C of the two allelic families and the first 20 aa of the C region, this for most strains and adjuvants. Strong immune responses were associated with GLA-SE adjuvant and its combination with other TLR agonists (CpG or GDQ) compared to alhydrogel and Montanide. Further, the elicited Abs were also capable of recognizing Plasmodium -derived MSP2 and inhibiting parasite growth in ADCI. Conclusion: The data provide a valuable opportunity to evaluate in mice different adjuvant and antigen formulations of a candidate vaccine containing both MSP2 D and C fragments. The formulations with GLA-SE seem to be a promising option to be compared with the alhydrogel one in human clinical trials.